Amplification at 9p in Cervical Carcinoma by Comparative Genomic Hybridization - Kowan J. Jee; Young Tak Kim; Kyu Rae Kim; Yan Aalto; Sakari Knuutila (Analytical Cellular Pathology)
DNA copy number changes were studied by comparative genomic hybridization on 10 tumor specimens of squamous cell carcinoma of cervix obtained from Korean patients. DNA was extracted from paraffin‐embedded sections after removal of non‐malignant cells by microdissection technique. Copy number changes were found in 8/10 tumors. The most frequent changes were chromosome 19 gains (n=6) and losses on chromosomes 4 (n=4), 5 (n=3), and 3p (n=3). A novel finding was amplification in chromosome arm 9p21‐pter in 2 cases. Gains in 1, 3q, 5p, 6p, 8q, 16p, 17, and 20q and losses at 2q, 6q, 8p, 9q, 10p, 11, 13, 16q, and 18q were observed in at least one of the cases.